Rapid development of interprofessional in situ simulation-based training in response to the COVID-19 outbreak in a tertiary-level hospital in Ireland: initial response and lessons for future disaster preparation. (2nd September 2020) - Contreras, Maya; Curran, Emer; Ross, Mark; Moran, Peter; Sheehan, Ann; Brennan, Aoife Marie; Cosgrave, David; McElwain, Jennifer; Lavelle, Claire; Lynch, Bonnie
Abstract : Introduction: The first case of COVID-19 in Ireland was diagnosed on 29 February 2020. Within the same week, our Department of Anaesthesia and Critical Care at University Hospital Galway began to tackle the educational challenge by developing an in situ interprofessional simulation programme to prepare staff for the impending outbreak. Principles and approaches used for simulation-based training: We describe principles applied to identify core educational and system engineering objectives to prepare healthcare workers (HCWs) for infection control, personal and psychological safety, technical and crisis resource management skills. We discuss application of educational theories, rationale for simulation modes and debriefing techniques. Development of the simulation programme: 3 anaesthesia (general, obstetric, paediatric) and 1 critical care silo were created. 13 simulated scenarios were developed for teaching as well as for testing workflows specific to the outbreak. To support HCWs and ensure safety, management guidelines, cognitive aids and checklists were developed using simulation. The cumulative number of HCWs trained in simulation was 750 over a 4-week period. Challenges and future directions: Due to the protracted nature of the pandemic, simulation educators should address questions related to sustainability, infection control while delivering simulation, establishment of hybrid programmes and support for psychological preparedness.